Diversification: Complementary Assets and Super Additive Synergy - SAFTIANA, Yulia; SULASTRI, SULASTRI; ISNURHADI, ISNURHADI; ADAM, Mohamad; MUTHIA, Fida (Journal of Advanced Research in Law and Economics, 2018)
Diversification is a strategy choice at the corporate level for a variety of reasons, including the benefits of economies of scope or the exploitation of complementary assets synergies. Although the two concepts of economies of scope and synergy are different constructs, it will ultimately lead to how diversification through complementary assets that can create value. Empirical testing has been done with the event study method using 117 manufacturing companies listed in Indonesia Stock Exchange to answer how the availability of financial assets and operations before diversification is invested during the diversification and its impact on performance after diversification. The result of the test using the structural equation method after satisfying the assumption of goodness of fit measurement parsimony, proves that the use of complementary assets at the time of diversification creates no value, with the synergy sensitivity value <1 for leverage, retained earning and replacement cost of investment and still contributes negatively on profitability one year after diversification.